Preparation and diagnosis rules Leno complexes with Ortho Hyderoxa Benzldaaan - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
I attended the new chief base of bilateral interaction Para Amino like 1 Phenyl 4 Bayrosolin 5 Online with Alsalesl Aldehid someone Allicand by careful analysis of the elements and infrared spectrum